Measuring Women's Empowerment in Rwanda - Abdou Musonera; Almas Heshmati (Institute for the Study of Labor (IZA), 2016)
This study examines the determinants of women's empowerment in Rwanda using data obtained from DHS 2010. A regression analysis is used to investigate the association between women's empowerment and its covariates. The study also uses a multinomial logistic regression to assess what determines households' decision-making and attitudes towards physical abuse of spouses. Variables of sources of empowerment such as education and media exposure were found to have a net positive association with women's empowerment while other variables such as residence and the age at first marriage were negatively associated with women's empowerment. Further analysis showed that the effects of education, age of the respondent, wealth and the number of children ever born remained strong conditions which effected households' decision-making and attitudes about physical abuse. In general, therefore, it seems that for women to fully realize their potential and rights, specific emphasis should be put on variables that increase their access to resources and knowledge such as education, employment for cash and media exposure but variables that are negatively associated with women's empowerment such as higher age at first marriage should also be taken into account.
Keywords: D63; D91; I15; I25; J12; 330; women's empowerment; physical abuses; household decision-making; Rwanda